Fracture characterization via computed tomography in Thoroughbred racehorses - Posukonis, Megan, author; Daglish, Jodie, author; Kawack, Christopher, author (Colorado State University. Libraries, 2018)
Fractures of the third metacarpal/tarsal bone remain the most common injuries of the Thoroughbred racehorse. There are currently no data exploring the trabecular bone mineral density relative to the propagating fracture line as a correlate to clinical outcome. This study aims to use computed tomography to map fracture lines and relative bone mineral density through de novo image analysis software that could be employed at the hospital level. We have identified significant differences in the sclerotic region density between spiral and unicortical fracture types, suggesting that computer-assisted measurement of this parameter could be used as a diagnostic tool in assessing fracture risk and outcome as standing CT screening tools increase in prevalence and accessibility for equine athletes. In the future we hope to further explore the utility of this modeling paradigm via 3-dimensional analysis.
258 - Megan Posukonis
Colorado State University, College of Veterinary Medicine, Department of Clinical Sciences, Equine Orthopedic Research Center.
Keywords: computed tomography; fracture; equine; bone mineral density; convex hull